Assistance in Preparation of the Operational Budget at the Noor Arsy Foundation in Gondanglegi District - Himmiyatul Amanah Jiwa Juwita; Risna Wijayanti; Yovita Leyla Pradipta; Atim Djazuli (Journal of International Conference Proceedings, 2022)
The assets of the foundation can be in the form of money or goods, whether it comes from donations, endowments, grants, will grants and other acquisitions that do not conflict with the Foundation's Articles of Association or the prevailing laws and regulations. The foundation must periodically make an accountability report for the funds obtained from donors in detail related to the planned use of funds receipts and expenditure plans. Foundation funding assistance is usually a non-permanent aid, so institutions will be very vulnerable to financial difficulties if the expenditure is greater than the incoming funds, especially during the current pandemic. Foundation management must be able to think critically in strategic financial plans for foundation funds, so that if the funds they have are limited they will be able to allocate them appropriately and efficiently